Light-chain fibroin of Galleria mellonella L - Zurovec, M; Vasková, M; Kodrík, D; Sehnal, F; Kumaran, A K (Molecular & general genetics, 1995)
The posterior section of Galleria mellonella silk glands contains two abundant mRNAs that are identical except for the non-coding tail, which includes either two (1.1 kb mRNA) or three (1.2 kb mRNA) consensus sequences for polyadenylation sites. The transcripts are 40% homologous in the coding as well as non-coding regions with the mRNA encoding light-chain fibroin (L-fibroin) in Bombyx mori; the deduced translation product shows 43% identity with the Bombyx L-fibroin peptide, with all three cysteines conserved. Amino acid analysis of the N-termini of Galleria silk proteins revealed that L-fibroin (25 kDa) occurs in two isoforms, the shorter one lacking the Ala-Pro dipeptide residue at its N-terminus. The 29 and 30 kDa Galleria silk proteins appear to be homologs of Bombyx silk component P25. The results suggest that evolutionary diversification of Galleria and Bombyx L-fibroins involves alternative polyadenylation and proteolytic processing sites.
Keywords: Fibroins; Molecular Sequence Data; Molecular Weight; hmyzí hormony; messenger RNA; Sequence Analysis, DNA; Sequence Homology, Nucleic Acid; sekvence aminokyselin; DNA, Complementary; Sequence Alignment; Sequence Homology, Amino Acid; molekulová hmotnost; Moths; alternativní sestřih; kukla; bourec; Poly A; Pupa; Bombyx; můry; Base Sequence; sekvence nukleotidů; Protein Conformation; komplementární DNA; zvířata; Alternative Splicing; RNA, Messenger; Amino Acid Sequence; poly A; fibroiny; sekvenční analýza DNA; larva; sekvenční homologie nukleových kyselin; Larva; molekulární sekvence - údaje; Insect Hormones; sekvenční homologie aminokyselin; sekvenční seřazení; konformace proteinů; Animals